Strengthening Students' Religious Character Education Through Character Apple Activities at SD Negeri Ngaliyan 01 - Handayani, Riskiya Putri; Sholihah, Baqiyatush; Fihris, Fihris (Jurnal Pendidikan Karakter, 2025)
This research provides an important contribution in understanding the application of character apples as a medium for forming students' religious values at SDN Ngaliyan 01 Semarang City. Apple activities carried out regularly have proven to be effective in helping students internalize religious values, such as discipline, honesty, cleanliness and concern for others. The results of this research are in line with the Value Theory developed by Milton Rokeach, which emphasizes the importance of habits and social support in forming fundamental values in individuals. Routine practices such as group prayer and conveying moral messages help internalize values in students. The research also identifies barriers, such as religious diversity and time constraints, and offers solutions. With evidence of the positive impact of character apples, this research provides guidance for schools and stakeholders to form a moral and spiritual generation. Apart from that, the role of teachers and school principals as role models is also emphasized as the main element in supporting the significant strengthening of students' religious values. This research not only strengthens religious character education efforts but can also be an inspiration for other schools in developing similar programs on an ongoing basis.